Natural resource or market seeking motive of China's FDI in asia? New evidence at income and sub-regional level. Issue 1 (1st January 2019) - Kamal, Muhammad Abdul; Ullah, Assad; Zheng, Jiajia; Zheng, Bowen; Xia, Huizhu
Abstract: Asia is a heterogeneous region including countries with distinct features in quite a few facets. This study is designed to unravel the motivations of Chinese FDI in 30 Asian countries (For list of countries see Appendix 1 .) during 2003–2016. For estimation, we utilised the Random effect (RE), Fixed effect (FE) and System-GMM (SGMM) methodologies. We transpired that both market and natural resource (mineral richness) seeking motives of Chinese FDI in the whole sample analysis. With respect to income group, we confirmed the market seeking FDI in both high and middle-income countries whereas, mineral richness is priority for Chinese FDI in middle-income group. Thus, Chinese firms targeted middle income developing economies to acquire non-fuel natural resources. Analogously, on the regional basis, the results show that in all regression models, GDP is positive and significant predictor, characterising market seeking FDI by Chinese firms in West, East and South East Asia. In resource seeking motive, among the two types of natural resources, mineral richness affect Chinese FDI positively in East & South East Asia. In a nutshell, seeking market is the common motive for Chinese FDI in the entire sample, whereas the resource seeking motive varies across the income groups and regions.